Micromachining using fiber laser for various metallic workpieces - Noor, Wazed Ibne; Rashid, Mir Akmam Noor; Saleh, Tanveer (2019)
Micromachining techniques are being used regularly in various engineering and production sectors such as Micro Electromechanical Systems, Aerospace, Automotive, Electronics and Biomedical industries. The technique for fabrication of 3D and 2D structures on micrometer levels is called micromachining. Highly energized laser beam is focused on a small region of the workpiece surface. As a result, it is heated up rapidly to sufficiently high temperatures, then the material starts to melt and/or vaporize from the surface. Consequently, material is removed due to combined effects of melting and vaporization. This phenomenon is called laser ablation. This process offers more control, high efficiency, precision and production rate, particularly for drilling microscopic holes in a variety of materials. The holes that are produced by laser beam drilling (LBD) can come with defects like taper, heat affected zone (HAZ) and solidification inside the hole. LBD performance is measured on different parameters such as size, taper, HAZ, recast layer of machined holes LBMM applies contactless method for removal of material so there is no concern for tool wear. The numerical values of the output parameters illustrate the effectiveness of LBD for various micromachining operations. Characterization of different parameters is done by SEM (Scanning Electron Microscope) machine to increase the accuracy and enhance observations.